Joachim Metallman’s project of philosophy of nature - Heller, Michał; Mączka, Janusz (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2010)
We analyse a manuscript, preserved in the Archives of the Polish Academy of Science and the Polish Academy of Science and Art in Cracow, containing Joachim Metallmann’s notes aimed at composing a project of a textbook or a series of lectures concerning philosophy of nature. He understood philosophy of nature as a sort of ontology and epistemology of nature whose starting point should be provided by the natural sciences.